Later achievement of infant motor milestones is related to lower levels of physical activity during childhood: the GECKO Drenthe cohort - Silvia I. Brouwer; Ronald P. Stolk; Eva Corpeleijn (BMC, 2019)
Abstract Background The aim of this study is to investigate whether age of infant motor milestone achievement is related to levels of physical activity (PA), weight status and blood pressure at age 4-7 years of age. Methods In the Dutch GECKO (Groningen Expert Center of Kids with Obesity) Drenthe cohort, the age of achieving the motor milestone 'walking without support' was reported by parents. Weight status and blood pressure were assessed by trained health nurses and PA was measured using the Actigraph GT3X between age 4 and 7 years. Results Adjusted for children's age, sex and the mother's education level, infants who achieved walking without support at a later age, spent more time in sedentary behaviour during childhood and less time in moderate-to-vigorous PA. Later motor milestones achievement was not related to higher BMI Z-score, waist circumference Z-score, diastolic or systolic blood pressure. Conclusion The results of this study indicate that a later age of achieving motor milestone within the normal range have a weak relation to lower PA levels at later age. It is not likely that this will have consequences for weight status or blood pressure at 4-7 years of age.